Antioxidant Potential and Known Secondary Metabolites of Rare or Underutilized Plants of Yucatan Region - Jonatan Jafet Uuh-Narvaez; Maira Rubi Segura-Campos; Oksana Sytar (Future Pharmacology, 2023)
The screening of rare plants from the Yucatan region and the known native plants in Mexico, that have been successfully introduced worldwide, has been conducted. Based on a literature analysis and a search of English and Spanish scientific information regarding botanical, plant biochemical, and antioxidant potential in databases such as Google Scholar, Scopus, Web of Knowledge, as well as the national databases of Mexico (Flora: Yucatan Peninsula (cicy.mx) and Especies endémicas|Biodiversidad Mexicana), rare or underutilized plants from the Yucatan region with antioxidant potential have been selected. The formulas of the most studied secondary metabolites of these selected rare plants are shown. Among the selected rare plants with antioxidant potential, the families Sapidaceae and Anacardiaceae had the highest number of representatives. Additionally, representatives from the families Annonaceae, Moraceae, Malpighiaceae, Solanaceae, Ebenaceae, Asteraceae, Ranunculaceae, and Leguminosae were also presented. The current scientific data analysis of selected rare plants from the Yucatan region, Mexico, provides significant background for their further use and introduction in not only the Yucatan region of Mexico, but also worldwide.